Research trends on communication of government in the world: A systematic literature review - Marwan Sabda, Afief (International Journal of Politics and Public Policy, 2025)
The purpose of this study is to gain knowledge and understanding of scientific advances related to government communication through publications added to the Scopus database. This study used 222 scientific papers from the Scopus database to conduct a systematic literature review as a research methodology. According to the survey, there was an increase in the total number of people reporting writing scientific articles on government communication between 2022 and 2023, from 107 in 2022 to 115 in 2023. The number of papers available in the Scopus database in 2022-2023 demonstrates this. The findings of this study have helped create a research agenda on government communication. A weakness of this study is that it only used articles from the Scopus database; therefore, its conclusions are limited in their ability to address global concerns related to government communication. Scientific publications from other reliable international databases, such as Dimensions Scholars and Web of Science, should be utilized in future studies.